Receivables Turnover, Leverage, Company Size and Profitability: An Empirical Study on Indonesian Financial Companies - Dwiastari, I Gusti Ayu Windy; Darmawan , Ari; Happy Sugiastusti, Reika (FIA UB, 2024)
This study aims to determine the effect of receivables turnover, leverage, and company size on the profitability of Financing Companies listed on the Indonesia Stock Exchange in 2016-2021. The type of research used in this study is explanatory reachers with a quantitative approach. This study used secondary data from the official website of the Indonesia Stock Exchange in the form of the company's annual financial statements. The population of this research is 16 finance companies, and the population was selected through purposive sampling techniques based on predetermined considerations that determined the number of samples to be as many as nine companies. The data analysis techniques used are descriptive analysis, classical assumption test, multiple linear regression test, determination test, and hypothesis test (t-test and F test), analyzed by SPSS version 25. The results of this study prove that the partial receivables turnover variable has a positive and significant effect on profitability. The leverage has a negative and significant effect on profitability. The size of the company has an insignificant effect on profitability. Simultaneously, receivables turnover, leverage, and company size variables significantly affect profitability.